ANALISIS KINERJA JEMBATAN GANTUNG PEJALAN KAKI DENGAN MENARA BAJA DAN MENARA KOMPOSIT MELALUI ANALISIS NUMERIK BERBASIS PERANGKAT LUNAK - Juni Indriani; Nurkhasanah Rina Puspita; Indi Rezki Uli Simanjuntak; Ricky Bakara; Agnes Br Manurung (Yayasan Nusantara Hasana Berdikari, 2025)
This study evaluates the structural performance of a Class I pedestrian suspension bridge using two pylon configurations steel and steel–concrete composite through numerical analysis with SAP2000. The design follows SE Menteri PU No.02/SE/M/2010, SNI 2833:2013, SNI 2833:2013, and SNI 1725:2016. The conceptual model is located at the Kampar River with a 100 m main span, 15 m side spans, and a 1.8 m width. Load cases include dead load, symmetric and asymmetric live loads, seismic loads for zone 4, and wind loads with a design speed of 35 m/s. Results show both models have similar structural responses, although the composite pylon provides higher stiffness. Results indicate that the structural responses of both models are very close, although the composite pylon exhibits higher stiffness. Differences in maximum deformation are minimal: 0.000034 m due to seismic loading, 0.000001 m due to wind, and 0.000003 m for girder deflection. Cable stresses also differ slightly, with values of 0.15 kN/m² for the main cables and 125.81 kN/m² for the backstays. Overall, the composite pylon is considered an efficient alternative for increasing stiffness without significantly altering the structural behavior.